Functions of CD1d-Restricted Invariant Natural Killer T Cells in Antimicrobial Immunity and Potential Applications for Infection Control - Kinjo, Yuki; Takatsuka, Shogo; Kitano, Naoki; Kawakubo, Shun; Abe, Masahiro; Ueno, Keigo; Miyazaki, Yoshitsugu (Frontiers in Immunology, 2018)
CD1d-restricted invariant natural killer T (iNKT) cells are innate-type lymphocytes that express a T-cell receptor (TCR) containing an invariant α chain encoded by the Vα14 gene in mice and Vα24 gene in humans. These iNKT cells recognize endogenous, microbial, and synthetic glycolipid antigens presented by the major histocompatibility complex (MHC) class I-like molecule CD1d. Upon TCR stimulation by glycolipid antigens, iNKT cells rapidly produce large amounts of cytokines, including interferon-γ (IFNγ) and interleukin-4 (IL-4). Activated iNKT cells contribute to host protection against a broad spectrum of microbial pathogens, and glycolipid-mediated stimulation of iNKT cells ameliorates many microbial infections by augmenting innate and acquired immunity. In some cases, however, antigen-activated iNKT cells exacerbate microbial infections by promoting pathogenic inflammation. Therefore, it is important to identify appropriate microbial targets for the application of iNKT cell activation as a treatment or vaccine adjuvant. Many studies have found that iNKT cell activation induces potent adjuvant activities promoting protective vaccine effects. In this review, we summarize the functions of CD1d-restricted iNKT cells in immune responses against microbial pathogens and describe the potential applications of glycolipid-mediated iNKT cell activation for preventing and controlling microbial infections.